Etiology of Congestive Heart Failure in Children - Ashbah Islam, Ayesha Hafeez, Tahira Aslam, Muhammad Anwar, Shazia Siddique, Arshad Rafique, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of common causes of congestive heart failure among children in a tertiary care hospital. Study Design: Cross-sectional study Place and Duration of Study: Department of Paediatrics Medicine, Services Hospital, Lahore from 1st January 2018 to 30th June 2018. Methodology: Ninety children were enrolled. Demographic information like name, age, gender, weight of child was noted. Complete blood count, echocardiography and chest X-ray were done. Children underwent assessment for presence of causes of congestive heart failure. Results: Fifty six (62.22%) were between 2-30 months of age whereas 34 (37.78%) were between 31-60 months of age with mean age 29.4±12.47 months. There were 40 (44.44%) males and 50 (55.56%) females. The causes of CCF were acute myocarditis in 39 (43.33%), congenital heart disease in 31 (34.44%) and severe anemia in 20 (22.33%). Conclusion: Acute myocarditis is one of the common causes of congestive heart failure in children aftersevere anemiaand congenital heart disease. Keywords: Congestive heart failure, Common causes, Acute myocarditis, Congenital heart disease, Severe anemia